EFEKTIVITAS PEMBELAJARAN DARING PROGRAM STUDI PENDIDIKAN EKONOMI - Asri Neli Putri; Suparmi Suparmi (Universitas Negeri Padang, 2020)
The Covid-19 virus has changed the learning process around the world, Efforts made during a pandemic are online learning. Where the online learning system can be done without having to meet face to face but through virtual classes through online media. The aim of this research is to get an overview of the implementation of online learning in the Economic Education Study Program of STKIP 'Aisyiyah Riau. The subjects in this study were all students of the Economic Education Study Program. The method of data collection is done by using the interview method via the zoom meeting app and by telephone. Data were analyzed in three stages, namely the process of data reduction, data presentation and drawing conclusions or verification. The results of this study indicate that: (1) Online learning was very effective in the Covid-19 period which could increase motivation and comfort in the learning process; (2) overall students already have the means to support online learning; (3) Quota fees that must be paid by students for online learning are quite expensive; (4) Online learning can reduce the spread of Covid-19 in STKIP 'Aisyiyah RiauKeywords : Effectiveness, Online learning, Covid-19